2020
DOI: 10.1002/gea.21816
|View full text |Cite
|
Sign up to set email alerts
|

The significance of aragonite in the interpretation of the microscopic archaeological record

Abstract: Aragonite is one of the metastable polymorphs of calcium carbonate and is commonly found at archaeological sites in the form of mollusk shells and speleothems. Other occurrences include corals, fish otoliths, seed endocarps, wood ash, and lime plaster. These materials contain microscopic embedded information of fundamental importance for the assessment of the state of preservation of the archaeological record, the reconstruction of paleoenvironments, the identification of pyrotechnological processes, and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 171 publications
(252 reference statements)
0
21
0
Order By: Relevance
“…In addition, the mineralogical preservation of aragonitic shells does not necessarily imply that the microstructure is unaltered (Toffolo, 2021), which is again evidenced in the SEM images (Fig. 9).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In addition, the mineralogical preservation of aragonitic shells does not necessarily imply that the microstructure is unaltered (Toffolo, 2021), which is again evidenced in the SEM images (Fig. 9).…”
Section: Discussionmentioning
confidence: 88%
“…Studies by ), Milano et al (2016), and Villagran (2014 for example have made important first steps towards understanding the various effects that different cooking methods, temperatures, and durations have on particular shell species; however, microstructural alterations also need to be explored. Studies also show that at normal earth surface pressure, together with carbonation at temperatures above 600 °C, pyrogenic aragonite in the shape of acicular crystals can form (Toffolo, 2021;Toffolo et al, 2017;Toffolo & Boaretto, 2014). These acicular crystals were present on some of the experimental samples that underwent flames and 600 °C temperatures but also on a couple of the coals and 400 °C samples.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Assuming fish otoliths form under equilibrium conditions, their stable isotope ratios of carbon (δ 13 C) and oxygen (δ 18 O) may therefore be used for the estimation of temperatures of their habitats (Fay, 1984; Morris & Kittleman, 1967). Being monomineralic (aragonitic), they can be screened for diagenetic effects based on the determination of the occurrence of secondary calcite using bulk mineralogical analyses (such as XRD or FTIR) and assessment of the degree of local structural ordering using micro Raman techniques (Toffolo, 2021). Previous studies employing the δ 18 O composition of otoliths demonstrated that the accretionary growth layers is in equilibrium with the water in which the host fish lives (Kalish, 1991b; Patterson et al., 2013; Thorrold et al., 1997).…”
Section: Introductionmentioning
confidence: 99%